DMC1 stabilizes crossovers at high and low temperatures during wheat meiosis - Draeger, Tracie N.; Rey, María-Dolores; Hayta, Sadiye; Smedley, Mark; Martin, Azahara C.; Moore, Graham (Frontiers in Plant Science, 2023)
Effective chromosome synapsis and crossover formation during meiosis are essential for fertility, especially in grain crops such as wheat. These processes function most efficiently in wheat at temperatures between 17-23 ℃, although the genetic mechanisms for such temperature dependence are unknown. In a previously identified mutant of the hexaploid wheat reference variety ‘Chinese Spring’ lacking the long arm of chromosome 5D, exposure to low temperatures during meiosis resulted in asynapsis and crossover failure. In a second mutant (ttmei1), containing a 4 Mb deletion in chromosome 5DL, exposure to 13 ℃ led to similarly high levels of asynapsis and univalence. Moreover, exposure to 30 ℃ led to a significant, but less extreme effect on crossovers. Previously, we proposed that, of 41 genes deleted in this 4 Mb region, the major meiotic gene TaDMC1-D1 was the most likely candidate for preservation of synapsis and crossovers at low (and possibly high) temperatures. In the current study, using RNA-guided Cas9, we developed a new Chinese Spring CRISPR mutant, containing a 39 bp deletion in the 5D copy of DMC1, representing the first reported CRISPR-Cas9 targeted mutagenesis in Chinese Spring, and the first CRISPR mutant for DMC1 in wheat. In controlled environment experiments, wild-type Chinese Spring, CRISPR dmc1-D1 and backcrossed ttmei1 mutants were exposed to either high or low temperatures during the temperature-sensitive period from premeiotic interphase to early meiosis I. After 6-7 days at 13 ℃, crossovers decreased by over 95% in the dmc1-D1 mutants, when compared with wild-type plants grown under the same conditions. After 24 hours at 30 ℃, dmc1-D1 mutants exhibited a reduced number of crossovers and increased univalence, although these differences were less marked than at 13 ℃. Similar results were obtained for ttmei1 mutants, although their scores were more variable, possibly reflecting higher levels of background mutation. These experiments confirm our previous hypothesis that DMC1-D1 is responsible for preservation of normal crossover formation at low and, to a certain extent, high temperatures. Given that reductions in crossovers have significant effects on grain yield, these results have important implications for wheat breeding, particularly in the face of climate change.